Heterogeneous formation of polar stratospheric clouds – Part 2: Nucleation of ice on synoptic scales - I. Engel (Atmospheric Chemistry and Physics, 2013)
This paper provides compelling evidence for the importance of heterogeneous nucleation, likely on solid particles of meteoritic origin, and of small-scale temperature fluctuations, for the formation of ice particles in the Arctic stratosphere. During January 2010, ice PSCs (polar stratospheric clouds) were shown by CALIPSO (Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observations) to have occurred on a synoptic scale (~1000 km dimension). CALIPSO observations also showed widespread PSCs containing NAT (nitric acid trihydrate) particles in December 2009, prior to the occurrence of synoptic-scale regions of ice PSCs during mid-January 2010. We demonstrate by means of detailed microphysical modeling along air parcel trajectories that the formation of these PSCs is not readily reconciled with expectations from the conventional understanding of PSC nucleation mechanisms. The measurements are at odds with the previous laboratory-based understanding of PSC formation, which deemed direct heterogeneous nucleation of NAT and ice on preexisting solid particles unlikely. While a companion paper (Part 1) addresses the heterogeneous nucleation of NAT during December 2009, before the existence of ice PSCs, this paper shows that also the large-scale occurrence of stratospheric ice in January 2010 cannot be explained merely by homogeneous ice nucleation but requires the heterogeneous nucleation of ice, e.g. on meteoritic dust or preexisting NAT particles. The required efficiency of the ice nuclei is surprisingly high, namely comparable to that of known tropospheric ice nuclei such as mineral dust particles. To gain model agreement with the ice number densities inferred from observations, the presence of small-scale temperature fluctuations, with wavelengths unresolved by the numerical weather prediction models, is required. With the derived rate parameterization for heterogeneous ice nucleation we are able to explain and reproduce CALIPSO observations throughout the entire Arctic winter 2009/2010.